CRITICAL REFLECTION TO ONE'S OWN PEDAGOGICAL PRACTICE (Scientific journal of the Fergana State University, 2026)
The article examines the process of professional development, which is a fundamental resource for building competence: learning one’s responsibilities and becoming competent are considered two sides of the same process. This aspect is related to the development of cognitive abilities and highlights the need for assessment that accounts for the “technology of time,” i.e., the gradual process of self-education. The duration of the process may vary among teachers, mainly due to individual differences and the characteristics of the work environment. Assessment requires consideration of the teacher’s own development and pedagogical training. From a scientific perspective, the methodology is embedded in a cognitive model that develops the skills teachers need to fulfill their responsibilities. It is assumed that a teacher’s activity reflects the realization of competence. Consequently, competence is never directly observed, but it manifests through the traces of the teacher’s activity. In the context of active intercultural information exchange, methods and technologies are changing rapidly, while at the same time new perspectives emerge, such as improving scientific culture, demonstrating professional autonomy, and ensuring a supportive organizational environment at the workplace.